A. \(f'\left( x \right) = \frac{{ - 4}}{{{{\left( {{e^x} - {e^{ - x}}} \right)}^2}}}\)
B. \(f'\left( x \right) = {e^x} + {e^{ - x}}\)
C. \(f'\left( x \right) = \frac{{{e^x}}}{{{{\left( {{e^x} - {e^{ - x}}} \right)}^2}}}\)
D. \(f'\left( x \right) = \frac{{ - 5}}{{{{\left( {{e^x} - {e^{ - x}}} \right)}^2}}}\)
A
\({\left( {\frac{{{e^x} + {e^{ - x}}}}{{{e^x} - {e^{ - x}}}}} \right)^\prime } = \frac{{\left( {{e^x} - {e^{ - x}}} \right)\left( {{e^x} - {e^{ - x}}} \right) - \left( {{e^x} + {e^{ - x}}} \right)\left( {{e^x} + {e^{ - x}}} \right)}}{{{{\left( {{e^x} - {e^{ - x}}} \right)}^2}}}\) \( = \frac{{ - 2{e^x}.{e^{ - x}} - 2{e^x}.{e^{ - x}}}}{{{{\left( {{e^x} - {e^{ - x}}} \right)}^2}}} = \frac{{ - 4}}{{{{\left( {{e^x} - {e^{ - x}}} \right)}^2}}}\)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247